2022
DOI: 10.1177/15394492221101846
|View full text |Cite
|
Sign up to set email alerts
|

Financial Acumen Improves After Financial Literacy Training in Individuals With Substance Use Disorder

Abstract: Financial literacy is a skill that may be affected by decreased cognitive processes that arise from substance use disorder. The aim of this mixed-methods study was to determine change in financial acumen after participating in a financial literacy program. Study participants were recruited from a drug and alcohol treatment center in the Southeastern United States. A total of 31 males participated. A t-test was conducted to compare the scores on the financial tests. There was a significant difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although, in this study, we found that the average debt was potentially lower than state averages compared to the general population (~USD 13,000), we attribute this largely to the fact that most individuals in OUD treatment are less likely to own a home or have large sums of debt from larger purchases such as cars [41]. Municipal recovery centers and addiction treatment centers could also offer additional resources to patients, such as financial literacy campaigns for recovery with upskilling resources for those trying to find work [20]. How to deploy financial literacy campaigns effectively for people in recovery should be further explored.…”
Section: Key Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although, in this study, we found that the average debt was potentially lower than state averages compared to the general population (~USD 13,000), we attribute this largely to the fact that most individuals in OUD treatment are less likely to own a home or have large sums of debt from larger purchases such as cars [41]. Municipal recovery centers and addiction treatment centers could also offer additional resources to patients, such as financial literacy campaigns for recovery with upskilling resources for those trying to find work [20]. How to deploy financial literacy campaigns effectively for people in recovery should be further explored.…”
Section: Key Resultsmentioning
confidence: 98%
“…Prior research has suggested that financial well-being has two primary dimensions: financial beliefs (i.e., perceptions and attitudes) and financial behaviors or actions [17][18][19]. Other researchers have theorized that financial literacy is critical in changing behaviors and beliefs [20]. There have been attempts to classify beliefs about personal finances and money into various typologies, primarily composed of factors related to how individuals feel about debt, spending versus saving, parental upbringing, emotions, and anxiety that money creates, as well as other dimensions [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation